Fatores que condicionam a formação de ambientes urbanos inovadores em cidades sustentáveis - Bichueti, Roberto Schoproni (2016)
Cities are at the heart of the debate on sustainable development. The urbanization over recent decades has brought with it many challenges around the urban sustainability. The cleaner energy generation, proper disposal of solid waste, urban mobility and the availability of green areas are some of goals in different agendas of sustainable cities. In this context, the adoption of management practices for sustainable urban development is able to produce urban conditions that may be mentioned: raising the quality of life and well-being of the population, reduction of environmental impacts and the adoption of a healthy lifestyle in the cities. This distinctive urban environment is able to provide, among other things, attracting qualified people, most social interaction between them and the attraction of investments. Several authors suggest that these factors, among others, may be associated with the generation of positive externalities that promote economic development and increase the ability to produce innovation. A qualified urban environment that values diversity, fosters creativity and enables the knowledge sharing can be considered suitable for the increased creativity and innovation. In this sense, the study aims at analyzing the importance of management practices for sustainable urban development to promote favorable urban conditions to the formation of innovative urban environments in sustainable cities. For this, a qualitative and exploratory research, through a case study was carried out. The case of Curitiba city has been studied, in view of its representativeness in urban sustainability, which enabled the analysis of the phenomenon in a context that allowed the achievement of the objectives. It was possible to know the city's characteristics and the key management practices for sustainable urban development conducted in Curitiba. Above all, it could be noted urban conditions, as a result of these practices, capable of favoring the creation of an innovative urban environment, among which are: (1) social integration and articulation between the actors; (2) Attraction of qualified companies; (3) adequate mobility and urban infrastructure; (4) attracting and retaining talented / skilled human capital; (5) high quality of life; (6) active cultural scene. Thus, as a sustainable city, Curitiba was demonstrated an urban environment that promotes such conditions, which create positive externalities that favor the increase in innovative capacity in their territory. We can see, yet, a closer association of these conditions with the activities related to the service sector, such as the creative economy. We can see, yet, a closer association of these conditions with the activities related to the service sector, such as the creative economy. The research presents evidences to confirm the theoretical presupposition of the study, namely: management practices for sustainable urban development are able to provide conditions for the formation of innovative urban environments in sustainable cities.